The problem of liberalism identity - Jokubaitis, Alvydas (Politologija, 1999)
The article deals with three problems related to the political doctrine of liberalism. The problems are put in as follows: at the outset, the substance of the concept of liberalism is introduced, the main challenges facing the identity of modern political philosophy of liberalism presented, and an attempt is made to highlight certain tendencies peculiar to the development of this philosophy.The normative core of the given political doctrine is characterized by means of the following five ideas - individual liberty, human rights, justice, and moral pluralism. Author refers to the concepts generated by J. Shklar, R. Rorty, J. Gray, J. Rawls, and J. Raz as the most significant challenges to the identity of the political philosophy of liberalism.Nowadays, the process during which the political ideologies merge urges the liberals to search for new philosophical perspectives unknown in the past. It is obvious that currently both conservatives and socialists have mastered most of the political principles which shaped the identity of liberal thinking. In such a situation liberals are forced naturally to look for the new ways of expressing their beliefs. They are no longer feared to use the concepts which have been generated by their ideological opponents. Moreover, they tend to take over certain elements of political thinking characteristic to conservatives and socialists.Currently, liberalism breaks its ties with a paradigm of ideological political thinking - it looks for a broader perspective of social phenomena, among which shared interest of liberals in respect to the community, common goods, and political culture seems to stand out as distinct features of the aforementioned tendency. The liberals remain steadfast in referring to the idea of individual autonomy as principal. However, nowadays in comparison to the reflections characteristic of the liberals living in the days of J. Bentham and J. S. Mill, they seem to replenish their knowledge with modern reality - the existence of a far more complicated interaction between the individual and collective norms.Save emphasizing the significance of political culture, the liberals (J. Rawls, J. Raz, and J. Gray) draw closer to conservatives, the proponents of a conventional political culture since E. Burke, plus, they regard the creation of ideological projects skeptically. One may state that with a liberal-democratic political system behind their shoulders, the liberals become more and more conservative.
Keywords: -